Building entrepreneurial interest: Exploring entrepreneurial competency and self-efficacy strategies in entrepreneurship education - Gunartin, Gunartin; Pratikto, Heri; Winarno, Agung; Restuningdiah, Nurika (LPMPP Universitas Negeri Yogyakarta, 2025)
The success of becoming an entrepreneur is inseparable from various aspects that influence and shape it: internal aspects, coaching and training, social environment, family, socio-cultural factors, and other factors. This study aims to examine the strategy of entrepreneurial competence and self-efficacy in building entrepreneurial interest through entrepreneurship education. The author used a qualitative descriptive analysis method. Data were collected through observation, interviews, literature review and documentation. The results showed that in implementing entrepreneurship education to the fostered residents there are internalized values of fostering entrepreneurial interest through fostering independence and fostering personality. These values are based on good practices to build the character of the fostered citizens to become entrepreneurs with good and responsible personalities. Values that are interpreted as reflections related to the relationship of life, life, and livelihood. The results also show that social attitudes towards entrepreneurship in fostered residents are influenced by discipline, self-efficacy, perseverance, patience, and prayer. Based on the economic aspects of the foster, residents could become entrepreneurs. The entrepreneurship education model that fosters independence and personality is a pillar that allows prisoners to have social and entrepreneurial skills and be economically independent.